Non-Vitamin K Antagonist Oral Anticoagulants Related Nephropathy - Kaewduangjun , Tor; Pathumarak, Adisorn (Journal of the Nephrology Society of Thailand, 2025)
Non-vitamin K oral anticoagulants (NOACs) are widely used for various indications, such as stroke prevention in atrial fibrillation. Previous data include numerous case reports of unexplained acute kidney injury associated with NOAC use. Kidney biopsies in these cases have revealed red blood cell obstruction in Bowman’s space and renal tubules. Risk factors for NOACs-related nephropathy include underlying chronic kidney disease, diabetes mellitus, hypertension, and pre-existing IgA nephropathy. A kidney biopsy is recommended to confirm the diagnosis in patients suspected of having NOACs-related nephropathy. The primary treatment is supportive care, which may include temporarily discontinuing the medication. In cases where supportive care alone is insufficient, additional treatments such as corticosteroids or NOAC-specific antidotes have been reported to provide some benefits.